Legal Bases of Protection of Specially Protected Territories - JANTASSOVA, Amina (Journal of Advanced Research in Law and Economics, 2019)
The deliberate development and location of specially protected natural areas will help to preserve, restore and consistently strengthen the protection of environmental objects that have special ecological, scientific and cultural value. The issues of preservation in a natural state of natural complexes and objects of genetic, environmental, scientific, cultural and educational significance are in the focus of attention of state bodies. The relevance of the study is due to the fact that one of the main problems of socio-economic development of Kazakhstan is to ensure the environmental safety of citizens, environmental protection and rational nature management. Currently, the legislative material has been replenished with a significant number of new regulatory acts and has undergone qualitative changes, defining a fundamentally new approach to regulating relations in the field of specially protected areas, such as preservation of natural complexes and objects.